Thai Text Resource: A Recommended Thai Text Set for Voice Quality Measurements and Its Comparative Study - Daengsi, Therdpong; Preechayasomboon , Apiruck; Sukparungsee , Saowanit; Wutiwiwatchai , Chai (KKU Science Journal, 2012)
This review paper briefly presents voice quality measurement overview, related English text sets used in measurement, an overview of the Thai language and Thai sounds, and the development of a Thai text set, called the Thai Text Set for Telephonometry (TTST). TTST has been compared with LOTUS which is a Thai corpus that has been used widely for language and speech processing research in Thailand. This paper presents that TTST is simple and similar to CID Sentences and some CUNY Sentences. Moreover, it is in compliance with ITU-T P.800 standard. Therefore, the TTST could be recommended to create speech samples for voice quality measurements in Thai environments, which use Thai for communication.